Examination of Postgraduate Theses on Career in Sports Sciences in Turkey - Hülya Bingöl, Hatice Okumuş, Erdal Bölükbaşi, Reşit Çifçi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In the historical process, research in the field of career development of athletes has evolved from research on the termination of sports career to studies in which the career is addressed towards a more holistic, life-long and multi-level approach26. In this context, the career phenomenon, which has been the research topic of many sports scientists for years, still maintains its popularity. In addition to many scientific articles, it is known that career issues are examined in postgraduate theses. Therefore, it is very important to examine the postgraduate theses investigating the career issue and to make inferences as a result of this, as it will contribute to the literature. Aim: The aim of this research is to examine the postgraduate theses on career in sports sciences in Turkey in terms of parameters such as thesis level, publication year, data collection tool, purpose and result. Methods: This research was designed using the systematic review method. Between 03.04.2022 and 17.04.2022, a total of 37 theses were reached as a result of the search made by scanning the keywords "kariyer" in Turkish and "career" in English by filtering the word "Sport" on the database of the National Thesis Center. As a result of the evaluations made, 34 postgraduate theses were included in the research. In order to record the data obtained by the researchers, using the Excel 2016 (Microsoft Office) program, the information obtained according to the classification made as the author of the research, the thesis level, the year of publication, the participant group, the data collection tool, the purpose and the result were recorded in the appropriate place in the table. Afterwards, the findings of the research were presented in graphics and tables. Result: According to the research findings, it has been determined that there are 6 doctorate and 28 master’s theses on career in sports sciences in Turkey (Graph 1). In addition, it was determined that the most published postgraduate theses were published in 2021 (Graph 2). Also according to the research findings, it has been determined that Semi-structured Interview Form is mostly used as a data collection tool in postgraduate theses published on career in sports sciences in Turkey (Table 1). When the participant groups of the studies were examined, it was determined that mostly athletes, sports managers, academicians and students studying in the field of sports sciences participated as participants (Table 2). When the theses included in the research were examined in terms of purpose and result, it was determined that subjects such as career planning, barriers encountered in career planning, career plans of athletes, dual career, professional career plans of sports science students, career satisfaction, the relationship of career with other subjects such as emotional intelligence and life satisfaction were frequently investigated (Table 2). Conclusion: As a result, it can be said that the number of postgraduate theses on careers in sports sciences is increasing in Turkey. In addition, it was determined that the researches were carried out with different participant groups, and in this context, it can be said that the researches have a wide spectrum. In addition to these results, it can be said that graduate theses also have very rich content in terms of purpose and results.